2011
DOI: 10.3390/atmos2030484
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Grid Use in Air Quality Modeling

Abstract: The predictions from air quality models are subject to many sources of uncertainty; among them, grid resolution has been viewed as one that is limited by the availability of computational resources. A large grid size can lead to unacceptable errors for many pollutants formed via nonlinear chemical reactions. Further, insufficient grid resolution limits the ability to perform accurate exposure assessments. To address this issue in parallel to increasing computational power, modeling techniques that apply finer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…However, the approach has not yet been routinely applied in an operational mode for long-term multi-pollutant air quality simulations over large domains and with hundreds of sub-grid scale plumes. Garcia-Menendez and Odman [48] provide additional information on the state-of-the-science of adaptive grid modeling and what the future holds.…”
Section: Adaptive Grid Modelingmentioning
confidence: 99%
“…However, the approach has not yet been routinely applied in an operational mode for long-term multi-pollutant air quality simulations over large domains and with hundreds of sub-grid scale plumes. Garcia-Menendez and Odman [48] provide additional information on the state-of-the-science of adaptive grid modeling and what the future holds.…”
Section: Adaptive Grid Modelingmentioning
confidence: 99%
“…(20), where second order differences are used for the spatial approximation and the time integration is executed using the so-called Crank-Nicolson method: and -refinement (right). Reprinted with permission from [76].…”
Section: A Simple Approach: the Finite Difference Methodsmentioning
confidence: 99%
“…All of the methods above can be further developed by applying a time-dependent discretization [76]. In practice, one uses a variable grid with finer resolution at locations where the numerical error is high (usually where the concentration gradient is large); this is called adaptive gridding.…”
Section: Further Numerical Detailsmentioning
confidence: 99%
“…However, some studies suggested that results of modeled concentrations were also significantly sensitive to grid resolution [14][15][16][17][18]. Jang et al [14] used a high-resolution version of the regional acid deposition model (HR-RADM) to simulate ozone (O 3 ) formation at different grid resolutions (20,40 and 80 km) and found that the use of coarser grid spacing tended to underpredict O 3 maxima because of the of O 3 precursor dilution and to overpredict O 3 minima because of the NO titration effect.…”
Section: Introductionmentioning
confidence: 99%
“…A better correlation of observations compared to predictions are shown when using fine resolution, and the influence of model resolution was more significant for air quality than for meteorology simulation [17]. Using a coarse grid resolution may produce large discrepancies in the results compared to a fine grid resolution since it cannot capture inhomogeneities in emission rates, meteorology and land cover, while using a fine grid resolution may cause the simulation to be inefficient because it can be considerably limited by calculation time [15,18]. Therefore, model simulation should be performed using the appropriate grid resolution to obtain reliable and acceptable predictions in terms of both accuracy and computational time.…”
Section: Introductionmentioning
confidence: 99%